2010
DOI: 10.2478/s11535-009-0079-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of environmental factors on weed species composition of cereal and stubble fields in western Hungary

Abstract: Multivariate analysis of data obtained from 184 cereal and stubble fields in low-input agricultural systems located in western Hungary was undertaken in order to asses environmental factors affecting weed species composition. For each variable, the gross and net effect on weed species composition was calculated. All variables considered in this study had a significant effect on weed species composition and explained 26.99% of the total variation. Most variation in species composition was explained by the aspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 20 publications
4
31
3
1
Order By: Relevance
“…Distribution and establishment of weed communities are affected by several factors including soil properties and weather attributes (Fried et al, 2008;Pinke et al, 2010;Lousade et al, 2013). Preference of a weed species for a particular soil property may increase or decrease density on different soils which are poor or rich in that particular soil property, respectively.…”
Section: Correlation Between Weed Vegetation and Soil Properties/weatmentioning
confidence: 99%
“…Distribution and establishment of weed communities are affected by several factors including soil properties and weather attributes (Fried et al, 2008;Pinke et al, 2010;Lousade et al, 2013). Preference of a weed species for a particular soil property may increase or decrease density on different soils which are poor or rich in that particular soil property, respectively.…”
Section: Correlation Between Weed Vegetation and Soil Properties/weatmentioning
confidence: 99%
“…Firstly, the relative importance of climatic variables and altitude was found to decrease with decreasing length of gradients and thus potentially decreases with smaller spatial scale of a study (Lososová et al 2004;Cimalová and Lososová 2009). However, the same variables are also known to decrease in their relative importance towards southern Europe as they are generally more favourable for the weed vegetation there (Holzner and Immonen 1982;Šilc et al 2009;Pinke et al 2010Pinke et al , 2012. Another interesting fact is that variables representing a geographical position or region usually affect species composition much more when they are expressed as eco-region or phytogeographical region (Andersson and Milberg 1998;Hallgren et al 1999;Leeson et al 2000;Šilc et al 2009) rather than purely as latitude and longitude (Fried et al 2008;Hanzlik and Gerowitt 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Substantial differences due to different phenological stages of the weed vegetation during the growing season are bound to appear when the survey includes spring and autumn sown crops (Hallgren et al 1999). Regarding the sampling season, it was found that even within the same crop more variation of the weed vegetation was explained by the season aspect (spring vs. summer) than by any other management or environmental parameter (Pinke et al 2010). For this reason, the sampling date (described, e.g.…”
Section: Sampling Seasonmentioning
confidence: 99%
See 1 more Smart Citation
“…Šilc et al (2009) showed that the most important parameter in South-Eastern Europe was phytogeography and the second was crop. Pinke et al (2010) suggest that the most variation in species composition was explained by the seasonal aspect. Altitude was the least important factor.…”
Section: Introductionmentioning
confidence: 95%